1985
DOI: 10.1055/s-0038-1660101
|View full text |Cite
|
Sign up to set email alerts
|

White Blood Cell Count and Haematocrit as Predictors of Coronary Recurrence after Myocardial Infarction

Abstract: SummaryBaseline white blood cell count (WCC) and haematocrit were examined in relation to recurrent coronary events and to all-cause mortality in 2026 persons enrolled in the first Persantin-Aspirin Reinfarction Study (PARIS-1) 2-60 months after myocardial infarction. WCC was strongly related to coronary recurrence (relative risk 3.5 for men with WCC ≥ 9 × 109/1 vs men with WCC < 5 × 109/1) and total mortality (relative risk 2.6). No such relationships were found for haematocrit. WCC correlated also with ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
35
0
1

Year Published

1987
1987
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(39 citation statements)
references
References 29 publications
3
35
0
1
Order By: Relevance
“…This was probably because of the association of sICAM-1 and leucocyte counts demonstrated in the control group. We suppose that the well-known 'smokers' leucocytosis' (Lowe et al, 1985;Schwartz and Weiss, 1994) may account for the elevated serum levels in smokers that lay in the same range as those of patients with localized NSCLC. This possibility should be more carefully considered in future studies, as smokers could be regarded as a more obvious control group for patients with lung cancer than healthy non-smokers.…”
Section: Discussionmentioning
confidence: 95%
“…This was probably because of the association of sICAM-1 and leucocyte counts demonstrated in the control group. We suppose that the well-known 'smokers' leucocytosis' (Lowe et al, 1985;Schwartz and Weiss, 1994) may account for the elevated serum levels in smokers that lay in the same range as those of patients with localized NSCLC. This possibility should be more carefully considered in future studies, as smokers could be regarded as a more obvious control group for patients with lung cancer than healthy non-smokers.…”
Section: Discussionmentioning
confidence: 95%
“…16,18 Furman et al 27 examined the association between WBC count and mortality using data from the Worcester Heart Attack Study. Consistent with the findings from our study, these investigators found that WBC count was significantly associated with in-hospital survival.…”
Section: Wbc Count and Crp In Acute Myocardial Infarctionmentioning
confidence: 99%
“…1 Different markers of inflammation, including C-reactive protein, interleukin-6, erythrocyte sedimentation rate, fibrinogen, and other acute phase proteins have been associated with coronary events (CEs). [2][3][4][5][6] Increased leukocyte count is a classic marker of chronic and acute inflammation, reflecting proliferation and recruitment of leukocytes to the vascular system. Elevated leukocyte concentrations have been associated with increased incidence of myocardial infarction and stroke.…”
mentioning
confidence: 99%
“…8,14 Approximately 30% of men who experience a first acute CE die within the first days, and most of them die suddenly without reaching the hospital. 15 Elevated concentrations of leukocytes have been associated with worse prognosis in subjects with clinically manifest CHD, 5 but there are limited data from population-based studies of case fatality, including cases who died out-of-hospital. It was reported that 5 acute phase proteins were associated with increased fatality in men who experienced a CE, 16 but it remains unknown whether raised concentrations of leukocytes affect the fatality of subsequent CEs.…”
mentioning
confidence: 99%